“We Should be Listening to Our Elders”: Evaluation of Transfer of Indigenous Knowledge between Anishinabe Youth and Elders - Kulmann, Kassandra (Scholarship@Western, 2012)
Indigenous knowledge (IK) (knowledge held by Indigenous peoples regarding local environments, ways of life and culture) can potentially improve health and environment conditions. This thesis examines IK transfer between Anishinabe Elders and youth. A knowledge translation intervention was applied to address community concerns regarding decline of IK transfer between Elders and youth. Youth were hired to participate in a summer school and interview Elders regarding environment and health issues. Qualitative interviews were conducted with youth before and after their internships to evaluate their experiences and IK uptake. The summer school and internships were effective for facilitating IK transfer between Elders and youth. Based on the methods and findings of this thesis, a framework was developed that outlines structures and relationships necessary for IK transfer. This framework displays that the structures were not sufficient for IK transfer; relationships built between all involved in the research process were integral to knowledge transfer.